2018
DOI: 10.1007/s00203-018-1550-y
|View full text |Cite
|
Sign up to set email alerts
|

Aliibacillus thermotolerans gen. nov., sp. nov.: a thermophilic and heterotrophic ammonia-oxidizing bacterium from compost

Abstract: A novel moderately thermophilic and heterotrophic ammonia-oxidizing bacterium, designated strain BM62, was isolated from compost in the thermophilic stage in Harbin, China. Phylogenetic analysis based on the 16S rRNA gene indicated that strain BM62 belongs to the family Bacillaceae within the class Bacilli and was most closely related to Alteribacillus iranensis X5B (only 94.6% sequence similarity). Cells of strain BM62 were Gram-positive, rod-shaped, motile by periflagella, catalase-positive and oxidase-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The pH in the BM62 T ‐added compost was obviously lower than that of the control treatment, particularly during the hyperthermic phase and the phase which the temperature was falling. Lower pH environment is likely to favor the retention of ammonia by strain BM62 T or other nitrifiers …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH in the BM62 T ‐added compost was obviously lower than that of the control treatment, particularly during the hyperthermic phase and the phase which the temperature was falling. Lower pH environment is likely to favor the retention of ammonia by strain BM62 T or other nitrifiers …”
Section: Resultsmentioning
confidence: 99%
“…Data from the polyphasic taxonomy study suggested that strain BM62 T should be classified as the type strain of the type species of a new genus within the family Bacillaceae for which the name Aliibacillus thermotolerans was proposed. And the naming part of strain BM62 T has been reported in another article . In this paper, the promotion of nitrogen retention by strain BM62 T inoculation during the composting of chicken manure and rice straw was evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/microorganisms10122355/s1, Table S1: Spore-forming genera of the order Bacillales; Table S2: The allocated genera to the family Bacillaceae; Table S3: list of (poly)extremophilic genera in the order Bacillales. References [20,22,26,256,258,295,297, are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%